2020
DOI: 10.1177/1932202x20910697
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Responsive Assessments of Spatial Analytical Skills and Abilities: Development, Field Testing, and Implementation

Abstract: A persistent problem in education is underrepresentation of certain cultural and linguistic groups such as American Indian, African American, and Hispanic, in special programs for exceptionally talented students, especially in science, technology, engineering, and mathematics (STEM). The spatial analytical task, a performance-based assessment with demonstrated reliability and validity as an instrument to identify exceptionally talented students, was included with new instruments created in the Cultivating Dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…The project was a collaboration between (a) faculty members at an R1 University in the Southwestern United States and (b) educators from four schools: two public schools, one charter school, and one Bureau of Indian Affairs grant school. Six assessments were included in the identification of students with exceptional talent in STEM: (a) math problem solving (Bahar & Maker, 2020), (b) spatial analytical performance assessment (Maker, 2020b), (c) physics concept maps (Maker & Zimmerman, 2020), (d) mechanical–technical performance assessment (Alfaiz et al, 2020), (e) life science concept maps (Maker & Zimmerman, 2020), and (f) the life science performance assessment. These six assessments were in three domains, math, physical sciences, and life sciences, and were measures of students’ domain-specific skills and abilities, creativity-relevant processes, and task motivation (Amabile, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The project was a collaboration between (a) faculty members at an R1 University in the Southwestern United States and (b) educators from four schools: two public schools, one charter school, and one Bureau of Indian Affairs grant school. Six assessments were included in the identification of students with exceptional talent in STEM: (a) math problem solving (Bahar & Maker, 2020), (b) spatial analytical performance assessment (Maker, 2020b), (c) physics concept maps (Maker & Zimmerman, 2020), (d) mechanical–technical performance assessment (Alfaiz et al, 2020), (e) life science concept maps (Maker & Zimmerman, 2020), and (f) the life science performance assessment. These six assessments were in three domains, math, physical sciences, and life sciences, and were measures of students’ domain-specific skills and abilities, creativity-relevant processes, and task motivation (Amabile, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this perspective, Sak and Maker (2006), in a study of mathematical problem-solving using the Discovering Intellectual Strengths and Capabilities while Observing Varied Ethnic Responses (DISCOVER) assessment, concluded that in elementary-age students, two standard deviations above the mean of domain-specific knowledge was a threshold for a one standard deviation above the mean of creativity in math. The DISCOVER math assessment (Bahar & Maker, 2011, 2020Maker, 1993Maker, , 2005, created in 1992 from a perspective similar to that of Silvia (2015), includes solving known problems with known operations and correct answers, accuracy in the solving of other types of problems (domain-specific knowledge and skills), and solving problems with multiple correct answers by applying mathematical concepts and operations in many and novel ways (domain-specific and domain-general creative processes; e.g., write as many problems as you can with the answer of 10).…”
Section: Creativity and Intelligencementioning
confidence: 99%
“…Based on field tests, instruments and observer instructions were revised again, and after field testing and additional revisions as needed, instruments were administered to the students in Grade 11 at the same partner schools. Development of each of these instruments and an in-depth description of their current form can be found in other publications (Alfaiz et al, 2020;Bahar & Maker, 2020;Maker, 2020;Zimmerman et al, 2020).…”
Section: Developing the New Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations